Quantitative, Competitive PCR Analysis of Porcine Circovirus DNA in Serum from Pigs with Postweaning Multisystemic Wasting Syndrome - Liu, Qiang (American Society for Microbiology, 2000)
A competitive PCR (cPCR) assay was developed for monitoring porcine circovirus (PCV) DNA in serum samples from piglets. The cPCR was based on competitive coamplification of a 502- or 506-bp region of the PCV type 1 (PCV1) or PCV2 ORF2, respectively, with a known concentration of competitor DNA, which produced a 761- or 765-bp fragment, respectively. The cPCR was validated by quantification of a known amount of PCV wild-type plasmids. We also used this technique to determine PCV genome copy numbers in infected cells. Furthermore, we measured PCV DNA loads in clinical samples. More than 50% of clinically healthy piglets could harbor both types of PCV. While PCV1 was detected in only 3 of 16 pigs with postweaning multisystemic wasting syndrome (PMWS), all the sick piglets contained PCV2. A comparison of the PCV2 DNA loads of healthy and sick animals revealed a significant difference, indicating that the development of PMWS may require a certain amount of PCV2.